Using evolutionary genomics, transcriptomics, and systems biology to reveal gene networks underlying fungal development. Issue 4 (September 2018) - Wang, Zheng; Gudibanda, Aditya; Ugwuowo, Ugochukwu; Trail, Frances; Townsend, Jeffrey P.
Abstract: Fungal model species have contributed to many aspects of modern biology, from biochemistry and cell biology to molecular genetics. Nevertheless, only a few genes associated with morphological development in fungi have been functionally characterized in terms of their genetic or molecular interactions. Evolutionary developmental biology in fungi faces challenges from a lack of fossil records and unresolved species phylogeny, to homoplasy associated with simple morphology. Traditionally, reductive approaches use genetic screens to reveal phenotypes from a large number of mutants; the efficiency of these approaches relies on profound prior knowledge of the genetics and biology of the designated development trait—knowledge which is often not available for even well-studied fungal model species. Reductive approaches become less efficient for the study of developmental traits that are regulated quantitatively by more than one gene via networks. Recent advances in genome-wide analysis performed in representative multicellular fungal models and non-models have greatly improved upon the traditional reductive approaches in fungal evo-devo research by providing clues for focused knockout strategies. In particular, genome-wide gene expression data across developmental processes of interest in multiple species can expedite the advancement of integrative synthetic and systems biology strategies to reveal regulatory networks underlying fungal development. Graphical abstract: Highlights: Diverse model species contribute to research on the evolution of fungal development. Transcriptomics facilitates study of developmental evolution for non-model fungi. Evolution of expression underlying evolved phenotypes can guide functional analysis. Bayesian networks predict promising experiments using integrative systems biology. The future of fungal evo-devo lies with systems biology of developmental traits.